Design of a GMSK demodulator / Azian Ahmad - Ahmad, Azian (1995)
The objective of this project is to study, design and circuit implementation of the Gaussian Minimum Shift Keying (GMSK) demodulator. The demodulator designed is of the coherent type that uses PLL in the clock and carrier recovery circuits which generate the clock signal. The purpose is to remove the intelligence-bearing signal from a modulated carrier and to reconstitute the signal that performed the modulation.